RANCANG BANGUN SISTEM DETEKSI KERUSAKAN BUAH APEL MERAH BERBASIS MIKROKONTROLER DENGAN PENDEKATAN LOGIKA FUZZY SUGENO - Juan Dini; Muhammad Ikhsan (Institut Teknologi Dirgantara Adisutjipto, 2026)
The manual apple sorting process still has limitations in terms of speed, objectivity, and accuracy, thus potentially reducing product quality in the market. This study aims to design and implement a microcontroller-based red apple damage detection system with a Sugeno Fuzzy logic approach using a TCS3200 color sensor and an MQ-135 gas sensor. Color and gas parameters are used as indicators of physical and chemical changes in the fruit due to the decay process. Sensor data is processed by a microcontroller to classify the condition of apples into three categories, namely good, slightly damaged, and severely damaged, and to control the sorting mechanism automatically. The research method is carried out through prototype design, experimental data collection, application of fuzzy rules, and system testing on 30 apple samples. The test results show that the system is able to classify 26 of the 30 samples correctly with an accuracy level of 86.7%. These findings prove that the combination of color and gas sensors with the Sugeno Fuzzy approach is effective for detecting apple damage automatically and has the potential to increase the efficiency of the sorting process in agriculture.